A wideband fast multipole accelerated singular boundary method for three-dimensional acoustic problems. (15th August 2018) - Qu, Wenzhen; Zheng, Changjun; Zhang, Yaoming; Gu, Yan; Wang, Fajie
Highlights: A new fast meshless method is developed for three-dimensional acoustic problems. The present method is efficient and accuracy for a wide range of frequencies. The present method avoids large number of element integrations in the BEM. A comparison of the present method and BEM for scattering model is provided. Abstract: In this paper, we present a new fast meshless method, called as wideband fast multipole singular boundary method (FMSBM), for three-dimensional acoustic problems. The wideband FMSBM applies a partial wave expansion formulation in low frequency regime and a plane wave expansion formulation in high frequency regime. The present method is efficient and accurate for a wider range of frequencies compared with the existing FMSBM approaches. In addition, the method avoids large number of element integrations in the boundary element method for resolving the complicated acoustic model, which can further reduce the computational complexity.